The role of demographic processes in the socio-economic development of the region (on the example of East Kazakhstan region) - Nuralina, K.T.; Niyazbekova, Sh.U. (BUKETOV BUSINESS REVIEW, 2021)
Objective: to identify the features of the demographic situation in the East Kazakhstan region, its role in demography in the socio-economic development of the region. Method: when analyzing the indicators of socio-economic development of the region using statistical and mathematical tools, general scientific methods of system analysis and synthesis were used. Findings: the article presents the results of the analysis of the demographic situation of the East Kazakhstan region. The analysis made it possible to identify the main problems of the demographic situation in the East Kazakhstan region, including the decline in the population over the past 30 years. Conclusions: the main factors affecting the demographic situation in the East Kazakhstan region are studied. As a result of the conducted research, priority measures were proposed to improve the demographic situation of the region, including overcoming violent conflicts; preventing man-made disasters; priority investment in healthcare, education, science, and strengthening the family